Assessment of the progress toward elimination of lymphatic filariasis in the Federal Capital Territory- Abuja, Nigeria - Amanyi-Enegela, Juliana Ajuma; Kumbur, Joseph; Burn, Nicholas; Sankar, Girija; Davies, Emmanuel; Ishaya, Rinpan; Ogoshi, Christopher; Ekweremadu, Bright; Omoi, Samuel; Qureshi, Babar (Frontiers in Tropical Diseases, 2022)
Lymphatic filariasis (LF) is a neglected tropical disease caused by threadlike worms (nematodes) that live in the lymphatic vessels of humans. Although three species of filarial parasites (Wuchereria bancrofti, Brugia malayi and Brugia timori) infect humans; 90% of infection is caused by Wuchereria Bancrofti and humans are its exclusive host. Nigeria is one of over 70 countries endemic for Lymphatic filariasis with an estimated 134 million people at the risk of infection. The Federal Capital Territory (FCT), which is endemic for LF, commenced mass drug administration (MDA) using ivermectin (IVM) and albendazole (ALB) in 2011. While MDA is continuing in two Area Councils, in 2020, we assessed the impact of MDA on LF prevalence in two area councils that had achieved five effective annual rounds of MDA. In 2010, a baseline mapping exercise was conducted in all six area councils of FCT-Abuja. The results revealed that four out of the six area councils were endemic for LF, with prevalence ranging from 1.0%-4.0%. The number of persons treated with ivermectin and albendazole in the four Area Councils was documented during annual MDA and population-based cluster surveys were conducted at least once in each area council during the five years of treatment, to verify the reported geographic and programme MDA coverage. This is the number treated divided by the total population eligible to receive treatment (usually <5years). The survey results confirmed that in two area councils (Abaji and Kuje) the coverage exceeded the target of 65% the while two other Councils did not reach the recommended coverage. A pre-transmission assessment survey (pre-TAS) was conducted in one sentinel site and at least one spot check site in Abaji and Kuje in 2019 and were found to have LF antigenemia (LF Ag) < 2% (range 0.0% to 1.99%). In 2020, transmission assessment surveys (TAS) were conducted in the two area councils that previously passed the Pre-transmission assessment survey. The results showed that the two Evaluation units had achieved the LF Ag threshold required to stop MDA. FCT has made significant progress towards LF elimination with two Area Councils qualifying to stop treatment. However, two other area councils still require a further two years of mass drug administration with effective MDA coverage before these area councils qualify for impact assessment.